Synthesis of antimicrobial silver nanoparticles through a photomediated reaction in an aqueous environment - Banasiuk R (Dove Medical Press, 2016)
Rafał Banasiuk,1,* Joanna E Frackowiak,2,* Marta Krychowiak,1 Marta Matuszewska,1 Anna Kawiak,1 Magdalena Ziabka,3 Zofia Lendzion-Bielun,4 Magdalena Narajczyk,5 Aleksandra Krolicka1 1Department of Biotechnology, Intercollegiate Faculty of Biotechnology, University of Gdansk and Medical University of Gdansk, 2Department of Pathophysiology, Medical University of Gdansk, Gdansk, 3Faculty of Materials Science and Ceramics, Department of Ceramics and Refractories, AGH-University of Science and Technology, Kraków, 4Institute of Chemical and Environment Engineering, West Pomeranian University of Technology, Szczecin, 5Faculty of Biology, Laboratory of Electron Microscopy, University of Gdansk, Gdansk, Poland *These authors contributed equally to this work Abstract: A fast, economical, and reproducible method for nanoparticle synthesis has been developed in our laboratory. The reaction is performed in an aqueous environment and utilizes light emitted by commercially available 1 W light-emitting diodes (λ =420 nm) as the catalyst. This method does not require nanoparticle seeds or toxic chemicals. The irradiation process is carried out for a period of up to 10 minutes, significantly reducing the time required for synthesis as well as environmental impact. By modulating various reaction parameters silver nanoparticles were obtained, which were predominantly either spherical or cubic. The produced nanoparticles demonstrated strong antimicrobial activity toward the examined bacterial strains. Additionally, testing the effect of silver nanoparticles on the human keratinocyte cell line and human peripheral blood mononuclear cells revealed that their cytotoxicity may be limited by modulating the employed concentrations of nanoparticles. Keywords: antimicrobial activity, green synthesis, nanocubes, nanospheres